PENGELOLAAN DANA ALOKASI KHUSUS TAHUN ANGGARAN 2012 DI DINAS PENDIDIKAN KABUPATEN DONGGALA - Hasan, Hasan (Katalogis, 2015)
This research aims at investigating the management of DAK on 2012 in education authority, Donggala regency. This research employs a qualitative approach with five selected informants. The techniques of data collection were library research, and field research with observation, interview, and documentation. The result of this research shows that the special allocation fund management on 2012 in education Authority, Donggala Regency, throught planning process, organizing process, Actuating process and controlling process. The implementation of the four management functions has run maximally, even though the planning process was lately done but the complation of the work could be finished on time. The emplementation was done by self management involving people participation based on school-based management.